2007
DOI: 10.1007/s10802-007-9163-y
|View full text |Cite
|
Sign up to set email alerts
|

A Dimensional Model of Psychopathology Among Homeless Adolescents: Suicidality, Internalizing, and Externalizing Disorders

Abstract: The present study examined associations among dimensions of suicidality and psychopathology in a sample of 428 homeless adolescents (56.3% female). Confirmatory factor analysis results provided support for a three-factor model in which suicidality (measured with lifetime suicidal ideation and suicide attempts), internalizing disorders (assessed with lifetime diagnoses of major depressive episode and post-traumatic stress disorder), and externalizing disorders (indicated by lifetime diagnoses of conduct disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
2
21
1
1
Order By: Relevance
“…While this number is lower than estimates found in existing studies of homeless adolescents (Rew et al, 2001; Yoder et al, 2008a; 2008b), a sizable number of youth reported psychological distress nonetheless. These findings confirm previous research involving homeless youth, and suggest there is a specific need for prevention and intervention efforts to target youth living with their families in temporary housing.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…While this number is lower than estimates found in existing studies of homeless adolescents (Rew et al, 2001; Yoder et al, 2008a; 2008b), a sizable number of youth reported psychological distress nonetheless. These findings confirm previous research involving homeless youth, and suggest there is a specific need for prevention and intervention efforts to target youth living with their families in temporary housing.…”
Section: Discussioncontrasting
confidence: 63%
“…Thoughts of self-harm and suicidal acts are highly associated with mental health disorders including major depressive disorder, posttraumatic stress disorder, and substance abuse (Yoder, Longley, Whitbeck, & Hoyt, 2008b), and are the third cause of death among youth 12 to 18 years of age (National Center for Injury Prevention and Control, 2009). In fact, exposure to violence and victimization has been linked to an increased risk for suicidal ideation among adolescents (Chemtob et al, 2011; Turner et al, 2012; Wolitzky-Taylor et al, 2009), as has youth substance abuse (Gould et al, 1998; Vermeiren et al, 2003, Wolitzky-Taylor et al, 2009).…”
Section: Adolescent Suicide Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies of both street and shelter recruited youth up to age 19 report that three-quarters of runaway and homeless youth meet life-time criteria for conduct disorder (Yoder, Whitbeck, & Hoyt, 2008; Yu, North, LaVesser, Obsborne, & Spitznagel, 2008). Yoder, Longley, Whitbeck and Hoyt (2008) noted that internalizing and externalizing disorders could indicate suicidality, highlighting the importance of screening this high risk group of adolescents for intervention.…”
Section: Introductionmentioning
confidence: 99%